2022
DOI: 10.1007/s11104-022-05685-x
|View full text |Cite
|
Sign up to set email alerts
|

Field scale plant water relation of maize (Zea mays) under drought – impact of root hairs and soil texture

Abstract: Background and aims Impact of drought on crop growth depends on soil and root hydraulic properties that determine the access of plant roots to soil water. Root hairs may increase the accessible water pool but their effect depends on soil hydraulic properties and adaptions of root systems to drought. These adaptions are difficult to investigate in pot experiments that focus on juvenile plants. Methods A wild-type and its root hairless mutant maize (Zea mays… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 60 publications
0
28
0
Order By: Relevance
“…Alternatively, the root hairs might influence leaf water potential dependent growth. Namely, when cumulative water extraction was normalized to shoot dry weight, Jorda et al (2022) detected higher water use efficiency of WT than rth3 maize [ 41 ]. Lower water use efficiency of rth3 could thus be explained by a more effective regulation of stomata in response to drought [ 50 ], which could also affect respiration rates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alternatively, the root hairs might influence leaf water potential dependent growth. Namely, when cumulative water extraction was normalized to shoot dry weight, Jorda et al (2022) detected higher water use efficiency of WT than rth3 maize [ 41 ]. Lower water use efficiency of rth3 could thus be explained by a more effective regulation of stomata in response to drought [ 50 ], which could also affect respiration rates.…”
Section: Discussionmentioning
confidence: 99%
“…Within the same field experiment, water transpiration data from Jorda et al (2022) demonstrated that severe water stress occurred just before tassel emergence (BBCH59 stage) [ 41 ]. Water stress is especially detrimental during the reproductive stages when water requirement is the highest [ 74 , 75 , 76 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental data on the role of soil texture and root hairs for the development of drought stress have been interpreted using modelling approaches at the laboratory scale for the juvenile phase (Köhler et al, 2022) and at field scale during the whole growing period in two consecutive years (Jorda et al, 2022). Jorda et al (2022) show that the root capacity was large enough to absorb all available soil water and that the onset of drought stress was primarily related to shoot size. Neither study could demonstrate a direct influence of roots hairs on soil-plant conductance for the selected maize genotypes, but proved an effect of soil texture on water use.…”
Section: Rhizosphere Traits and Water Uptakementioning
confidence: 99%
“…Root system architecture is important in natural and managed ecosystems (i.e., forests, pastures, and rangelands), but particularly pertinent to crop production systems, as they are more intensively managed with added inputs (i.e., agrochemicals and irrigation) and improved seed making the latter indispensable for human well-being and progress (Lynch, 2022). Crop growth and yield depend on the ability of the root system to explore, forage, and secure edaphic resources (Qiao et al, 2018; Chen et al, 2022; Jorda et al, 2022). However, root phenotyping research has lagged behind its aboveground counterpart due to the challenging nature of direct selection of root traits under field conditions, which because root systems are underground, requires significant logistical and infrastructure costs, time, and management considerations (Smith and De Smet, 2012; Thomas et al, 2016).…”
Section: Introductionmentioning
confidence: 99%